2011
DOI: 10.1159/000333132
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Plasma Progranulin Cutoff Value for Predicting Null Progranulin Mutations in Neurodegenerative Diseases: A Multicenter Italian Study

Abstract: Background: Recently, attention was drawn to a role for progranulin in the central nervous system with the identification of mutations in the progranulin gene (GRN) as an important cause of frontotemporal lobar degeneration. GRN mutations are associated with a strong reduction of circulating progranulin and widely variable clinical phenotypes: thus, the dosage of plasma progranulin is a useful tool for a quick and inexpensive large-scale screening of carriers of GRN mutations. Objective: To establish the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 49 publications
11
48
1
3
Order By: Relevance
“…In this group of mutation carriers, no relation could be established between serum PGRN levels and age at onset of symptoms, as the 2 patients with the lowest levels (cases 1 and 3) exhibit the lowest (43 years) and highest age of onset (63 years). This result disagrees with a large multicenter study [54], where PGRN null mutation carriers with the lowest PGRN levels showed a slight anticipation of disease onset. Interestingly, patients carrying the same mutation had similar serum PGRN levels (g.2263_2264dupGT < g.2631delG < g.1932_1933dupCC < g.2271delC), however, as already reported by Schofield et al [52] in 2010, the position of the mutation did not seem to be related with the level of serum PGRN, as mutations in exon 9 resulted in the lowest and highest serum PGRN levels within our group of PGRN mutation carriers.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this group of mutation carriers, no relation could be established between serum PGRN levels and age at onset of symptoms, as the 2 patients with the lowest levels (cases 1 and 3) exhibit the lowest (43 years) and highest age of onset (63 years). This result disagrees with a large multicenter study [54], where PGRN null mutation carriers with the lowest PGRN levels showed a slight anticipation of disease onset. Interestingly, patients carrying the same mutation had similar serum PGRN levels (g.2263_2264dupGT < g.2631delG < g.1932_1933dupCC < g.2271delC), however, as already reported by Schofield et al [52] in 2010, the position of the mutation did not seem to be related with the level of serum PGRN, as mutations in exon 9 resulted in the lowest and highest serum PGRN levels within our group of PGRN mutation carriers.…”
Section: Discussioncontrasting
confidence: 99%
“…We observed a good correlation between serum PGRN levels determined by both kits and the levels obtained with the AdiPogen kit are in line with the ones previously reported in the literature [52,55]. Moreover, the cut-off value for the discrimination between PGRN null mutation carriers and non-carriers obtained by the Adipogen kit was very similar to the one reported by others [52,54]. Despite the method used for establishing the cut-off levels for the R&D kit (ROC curve analysis to differentiate between PGRN null mutation carriers and non-carriers vs. -2 SD of the mean control level), the value was very similar: 23.6 vs. 24.4 ng/ml in serum and 20.5 ng/ml for both methods in plasma and a 100% accuracy in determining PGRN null mutations was achieved.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While previous research mainly focused on the role of progranulin as a biomarker and predictor of GRN -mediated FTD [3,4,26,27], the contribution of progranulin to GRN -negative FTD remains to be elucidated. Here, we investigated progranulin levels in the CSF of a carefully selected FTD cohort that was negative for mutations in GRN and other dementia genes, as demonstrated by WES.…”
Section: Discussionmentioning
confidence: 99%